2020
DOI: 10.1016/s2666-5247(20)30062-8
|View full text |Cite
|
Sign up to set email alerts
|

Ledipasvir plus sofosbuvir in pregnant women with hepatitis C virus infection: a phase 1 pharmacokinetic study

Abstract: Summary Background Hepatitis C virus (HCV) infection is increasing among pregnant women because of the opioid epidemic, yet there are no interventions to reduce perinatal HCV transmission or to treat HCV during pregnancy. Physiological changes in pregnancy alter the pharmacokinetics of some medications; thus, our aim was to compare the pharmacokinetic parameters of ledipasvir 90 mg plus sofosbuvir 400 mg during pregnancy with non-pregnant women. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 25 publications
0
71
0
2
Order By: Relevance
“…Clinical trials are ongoing to test DAA safety and efficacy, and treatment during pregnancy may be a possibility in the future. ( 14 , 15 ) Currently, women can be linked to HCV care for treatment after pregnancy and cessation of breastfeeding.…”
mentioning
confidence: 99%
“…Clinical trials are ongoing to test DAA safety and efficacy, and treatment during pregnancy may be a possibility in the future. ( 14 , 15 ) Currently, women can be linked to HCV care for treatment after pregnancy and cessation of breastfeeding.…”
mentioning
confidence: 99%
“…To date, two studies with a small number of patients showed no safety concerns for using sofosbuvir during pregnancy and high sustained virological response when using ledipasvir/sofosbuvir 6,10 . Although ribavirin is contraindicated during pregnancy based on animal data showing teratogenic and/or embryocidal effects, none of these effects were reported among the studied cohort of five patients who received ribavirin in combination with SOF/DCV or paritaprevir/ritonavir/ombitasvir.…”
Section: Discussionmentioning
confidence: 90%
“…A phase 1 trial assessing ledipasvir plus sofosbuvir for the treatment of chronic HCV infection during pregnancy showed 100% cure rates, large declines in viral loads within 10 to 21 days of starting treatment, and no clinically meaningful adverse effects on the mother/infant dyad. 56 In the meantime, until more data exist, if a patient becomes pregnant while taking one of the DAA therapies, they should be counseled that animal data do not suggest teratogenic risk, but human data are lacking. 1 In these scenarios, shared decision-making regarding risks and benefits of cessation vs continuation should occur.…”
Section: Should Hepatitis C Virus Be Treated During Pregnancy?mentioning
confidence: 99%